Tearfilm immunoglobulin E (IgE) level in vernal keratoconjunctivitis by ELISA - Pokharel, S; Shah, DN; Joshi, SN; Choudhary, M (Kathmandu University Medical Journal, 2010)
Background: Vernal keratoconjunctivitis (VKC) is recurrent chronic allergic conjunctivitis occurring in the prepubertal age-group with secondary involvement of the cornea and is self-limiting in character. The disease is prevalent worldwide but it shows predominance in the areas with dry and warm climate including the South Asia. VKC represents about 3% of the serious ophthalmic disease in some parts of the world where the prevalence is rate is high.Type I hypersensitivity reaction which is IgE-dependent and type IV hypersensitivity reaction have been implicated for the pathogenesis VKC. Objective: To determine level of immunoglobulin E (IgE) in the tear film of patients with Vernal Keratoconjunctivitis (VKC) attending outpatient department of BP Koirala Lions Centre for Ophthalmic Studies (BPKLCOS). Materials and methods: Thirty-four VKC patients and thirty-four controls were included in this study. Tear samples were collected using micro- capillary glass tube method and tear IgE levels were measured using an enzyme - linked immunosorbent assay (ELISA). Results: There was high concentration of tear IgE level in VKC (95.09IU/ml) than in controls (1.63IU/ml) though the difference was not statistically significant (p=0.16). No statistically significant difference was observed in male and female gender within VKC group and when compared with control group (in male group, p=0.21 and in female group, p=0.26). There was no statistically significant difference observed in tear IgE level in different age groups within VKC group and when compared with control group (p=0.30). The result did not show any significant difference in tear IgE level with respect to the duration of the disease (p=0.23).There was no statistically significant difference in tear IgE level with different episodes of VKC (p=0.69). No statistically significant difference of IgE concentration in tear was seen among different types of VKC (p=0.53) and grades of tarsal and limbal papillae (p= 0.72). Conclusion: There was high concentration of tear IgE level observed in VKC. Key words: Vernal keratoconjunctivitis; Tearfilm; IgE level; Type I hypersensitivity reaction; Type IV hypersensitivity reaction. DOI: 10.3126/kumj.v7i2.2700 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26, 104-108